Impact of different harvest times on yield and quality of summer savory (Satureja hortensis L.) genotypes - Ayse Ozlem Tursun (PLoS ONE, 2025)
Summer savory (Satureja hortensis L.) is a plant of the Lamiaceae family that grows in various ecological regions of the world. It is one of the medicinal-aromatic plants with huge economic value. The objective of this study was to determine the yield and quality of eight different summer savory genotypes, harvested at three different developmental stages, i.e., beginning of blooming, 40–50% blooming and full bloom stage. A field experiment was conducted during 2021 and 2022, and parameters related to growth, yield, and essential oil content were recorded. The maximum plant height, fresh and dry herb yield, dry leaf yield and essential oil content were obtained at the full bloom stage. The highest fresh herb yield was attained by genotype G6 and G7during the first and second year, respectively, while genotype G7 produced the highest dry herb and dry leaf yield during both years. The highest essential oil yield was obtained from genotype G8 and G7 in the first and second year of the study, respectively. Carvacrol, γ-terpinene, α-terpinene and p-cymene were the most abundant essential oil components observed in summer savory genotypes harvested at different developmental stages. The frequently detected component in the essential oil was carvacrol, which was recorded at 40–50%blooming period. The results of the current study proved that the most suitable period for harvesting summer savory genotypes was full blooming period in terms of yield values, and 40–50% blooming period for extracting essential oil especially carvacrol.